The Impact of Body Mass Index and Weight Changes on Disability Transitions and Mortality in Brazilian Older Adults - Flávia Cristina Drumond Andrade; Ahmad Iqmer Nashriq Mohd Nazan; Maria Lúcia Lebrão; Yeda Aparecida de Oliveira Duarte (Journal of Aging Research)
The aim of this study was to examine the association between body mass index and weight changes on disability transitions and mortality among Brazilian older adults. Longitudinal data from the Health, Well-Being, and Aging in Latin America and the Caribbean Study conducted in São Paulo, Brazil (2000 and 2006), were used to examine the impact of obesity on disability and mortality and of weight changes on health transitions related to disability. Logistic and multinomial regression models were used in the analyses. Individuals who were obese were more likely than those of normal weight to have limitations on activities of daily living (ADL), instrumental activity of daily living (IADL), and Nagi's limitations. Obesity was associated with higher incidence of ADL and IADL limitations and with lower recovery from Nagi's limitations. Compared to those who maintained their weight, those who gained weight experienced higher incidence of ADL and Nagi's limitations, even after controlling for initial body mass index. Higher mortality among overweight individuals was only found when the reference category was “remaining free of Nagi limitations.” The findings of the study underline the importance of maintaining normal weight for preventing disability at older ages.